Investigation of five common mutations on Phenylalanine Hydroxylase Gene of Phenylketonuria Patients from Two Provinces in North of Iran - Daniel Zamanfar; Hossein Jalali; Mohammad Reza Mahdavi; Morteza Maadanisani; Hossein Zaeri; Eynollah Asadpoor (International Journal of Preventive Medicine, 2017)
Background: There are more than 500 different mutations on phenylalanine hydroxylase (PAH) gene that is responsible for phenylketonuria (PKU) diseases and the spectrum of these mutations is varied in different populations. The main clinical manifestation of untreated patients is severe mental retardation. The PAH gene, that is 90 kb long, is consisted of 13 exons and 12 introns. The aim of the present study was to identify the frequency of five common mutations on PAH gene among patients with PKU in Mazandaran and Golestan provinces including c.1066-11G>A, p. R261Q, p. R252W, p. R261X, and c.1200 + 1G>C. Methods: Forty unrelated PKU patients, that 22 of them, were from Mazandaran and 18 of them from Golestan provinces were enrolled in the study. Genomic DNA was extracted from leukocytes using Qiagen DNA extraction kit and polymerase chain reaction - restriction fragment length polymorphism method was applied to detect five common mutations. Results: Three out of the 5 investigate mutations were identified among the patients. The c.1066-11G>A mutation has the highest frequency (27.5%) among the patients and the frequency of p. R261Q and p. R261X mutations were 3.75 and 1.25%, respectively. In Golestan province, only c.1066-11G>A mutation was observed in investigated alleles. Conclusions: The high frequency of c.1066-11G>A mutation in Golestan province may be related to genetic drift, founder effect, and consanguinity.